Unveiling revised North Korean English textbooks : language, ideology, and internationalisation - Ahn, Hyejeong; Lee, Hyejin (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examines the visual and textual representations of three revised national junior middle English textbooks as part of Kim Jong Un’s educational reform and aims to answer three questions: To what extent have the revised English textbooks i) fulfilled their proposed goal of improving North Koreans’ practical English skills? ii) remained ideologically driven propaganda tools and iii) how the internationalisation of English is presented in these textbooks. The results indicate that these textbooks powerfully reinforce the notion of the superiority of North Korea and promote the cult system of the Kims. The textbooks are highly localised and absent of international content. This study highlights that North Korean English textbooks are not designed to teach international communication in English but to equip students with certainty about the superior status of North Korea. Although this study focuses on North Korea, it can prompt a critical re-examination of the biases contained in international English textbooks, which sensationalise a “bright” view of Western societies.